Combination of traditional Chinese medicine and standard biomedical treatment for rosacea: a systematic review and a meta-analysis - Yu, Ruoxi; Li, Shuyan; Yang, Yuting; Xie, Chunguang; Chen, Qiu; Liu, Ya; Peng, Sihan (Frontiers in Pharmacology, 2024)
Background: A combination of standard biomedical treatment and traditional Chinese medicine (TCM) has been suggested as a therapeutic approach for rosacea that may significantly lower the recurrence rate and clinical symptom scores. We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the impact of this combination treatment on clinical symptom and TCM syndrome scores, as well as on the scores of the Dermatology Life Quality Index (DLQI), erythema index (EI), and interleukin 37 (IL-37) levels in patients with rosacea. Methods: The PROSPERO registration number for the study is CRD42023472737. We systematically searched the PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Database, China Biomedical Medicine database (CBM), and the VIP information resource integration service platform (cqvip) databases for RCTs (published from the beginning to September 2023, regardless of the language used) that compared the TCM and standard biomedical treatment combination treatment to conventional anti-rosacea treatments. Our primary outcomes comprised the clinical symptom and TCM syndrome scores, and the scores of DLQI, EI, and IL-37 levels. We used a random-effects model to evaluate the pooled data. Results: We identified 260 studies. Of these, 13 eligible studies were employed for analysis (N = 1348 participants). Compared with other anti-rosacea treatments, the TCM and standard biomedical treatment combination treatment yielded an improved mean reduction in the clinical symptom score –2.24% (95%CI[–3.02to–1.46], p<0.00001), TCM syndrome score –4.42 (95%CI[–5.33to–3.50], p<0.00001), and the score of DLQI of –2.55 (95%CI[–3.73to–1.36], p < 0.00001), EI of –151.97(95% CI[–276.59to–27.36], p<0.00001), and IL-37 level –4.23 (95% CI [–4.95 to –3.51], p=0.854), as well as in the overall effective rate (risk ratio (RR)=1.25(95%CI [1.18, 1.32], p=0.994) and the recurrence rate=0.27(95%CI [0.15, 0.46], p=0.297). Conclusion: The TCM and standard biomedical treatment combination treatment can provide a better outcome, including a reduction in the TCM syndrome and clinical symptom scores, and in the scores of DLQI, EI, and IL-37. Hence, this combination is a viable and more effective therapeutic approach for rosacea. However, these results should be considered cautiously because of uncertain evidence and the low quality of the study reports considered in this meta-analysis.